2006
DOI: 10.1016/j.acn.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical diseases: Do true neuropsychological differences exist?☆

Abstract: Previous work examining the cortical-subcortical distinction as it relates to cognitive patterns has not typically used genetic confirmation to identify these groups, controlled for age, or used a comprehensive battery to assess specific cognitive abilities. The present study is the first to include only genetically confirmed Familial Alzheimer's disease (FAD) and Huntington's disease (HD) patients to evaluate this distinction. Ten patients with FAD, 11 patients with HD, and 17 matched healthy individuals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
1
7
1
1
Order By: Relevance
“…The HD patients in the current study performed very differently than the AD patients of Duff et al (2008), but very similarly to the PD with dementia patients of Beatty et al (2003). Although this distinction of cortical/subcortical profiles is not definitive within neuropsychology (Arango-Lasprilla, et al, 2006; Salmon & Filoteo, 2007), two of the subcortical conditions (i.e., HD and PD) were separated from the cortical condition (i.e., AD) on the RBANS. The patients with MS, which also reflect a more prominent subcortical condition, were considerably higher functioning than the HD patients, although the two groups did perform comparably on tasks of immediate and delayed memory and language.…”
Section: Discussioncontrasting
confidence: 53%
“…The HD patients in the current study performed very differently than the AD patients of Duff et al (2008), but very similarly to the PD with dementia patients of Beatty et al (2003). Although this distinction of cortical/subcortical profiles is not definitive within neuropsychology (Arango-Lasprilla, et al, 2006; Salmon & Filoteo, 2007), two of the subcortical conditions (i.e., HD and PD) were separated from the cortical condition (i.e., AD) on the RBANS. The patients with MS, which also reflect a more prominent subcortical condition, were considerably higher functioning than the HD patients, although the two groups did perform comparably on tasks of immediate and delayed memory and language.…”
Section: Discussioncontrasting
confidence: 53%
“…Still it is a matter of debate whether creating an artificial border between 2 interconnecting parts of the brain is useful for daily diagnosis and treatment of patients. Arango-Lasprilla et al [44] suggested that the distinction between cortical and subcortical manifestation might not be clinically meaningful because patients with AD and HD appear to have similar neuropsychological profiles, especially in later stages. Bonelli and Cummings [7] suggested the establishment of the concept of frontal-subcortical dementia, as subcortical dementia shows frontal signs due to the close interconnections between basal ganglia and frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…One clue may be the diffuse nature of brain dysfunction prone to disturb highly distributed neural networks like the attention network, and the diffuse neurochemical changes these two pathologies may entail (Arciniegas, 2003;Bennouna, Greene, & Defranoux, 2005Carlsson, 2006). Arguments suggesting that diffuse neuropathology may result in common cognitive impairments come from comparisons among neurodegenerative diseases (Arango-Lasprilla, Rogers, Lengenfelder, Deluca, Moreno,& Lopera, 2006;Claus & Mohr, 1996). Yet, we can only speculate as to whether there is a common neural origin, and whether this would be due to the diffuse nature of brain dysfunction.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 92%